A Multi-Layer Grant-Free NOMA Scheme for Short Packet Transmissions - Abbas, Rana; Shirvanimoghaddam, Mahyar; Yonghui Li; Vucetic, Branka (2018 IEEE Global Communications Conference (GLOBECOM), 2018)
In this paper, we propose a multi-layer grant-free non-orthogonal multiple access scheme for short packet transmissions. In every time slot, users choose a layer randomly and independently of other users. Each layer corresponds to a code book, and users in each layer utilize the same code book and perform power control such that they have the same received power level at the Access Point (AP). Users of the same layer also choose the same pilot sequence that is transmitted with their code word, together with all users from other layers. The AP uses the pilot sequences to detect the layers selected and estimate the number of users in each layer. Using this information, the AP first separates the codewords corresponding to the different layers. Then, users of the same layer are decoded jointly. Based on this, we formulate an optimization problem to find the power levels that maximize the reliability of the system, i.e., the probability that an arbitrary user is decoded successfully, subject to some power and decoding complexity constraints. The problem is found to be non-linear and very complex. We propose some approximations that allow us to use mixed-integer linear programming (MILP). Numerical results show that the multi-layer setup can support a larger load with higher power efficiency for the same reliability and decoding complexity requirements.